Recent advances in the treatment of polycythemia vera. Issue 8 (3rd July 2022) - Duek, Adrian; Berla, Maya; Ellis, Martin H.
Abstract: Polycythemia vera (PV) has long been recognized as a disease characterized by excess blood cell production leading to thromboembolic phenomena. While the focus of treatment is on prevention of thromboembolic complications, achieved by hematocrit control and administration of low dose aspirin, attention has begun to shift to other elements of this chronic neoplasm, namely symptom control and arrest of disease progression. Clearly, phlebotomy is not able to accomplish these goals, and the ability of cytoreductive agents such as hydroxyurea (HU), to influence these elements of the disease is limited. Novel and repurposed drugs have recently entered this space, based on promising initial studies demonstrating their effects on biologic outcomes such as JAK2 V617F variant allele frequency (VAF). In this review, we present updated results of randomized clinical trials of pegylated interferon (IFN) and ruxolitinib and summarize emerging data from early phase trials of novel agents in PV.